Program Bimbingan Karir untuk Mengembangkan Kemampuan Membuat Pilihan Karir Peserta Didik - Muhibu Abivian; Amin Budiamin; Mubiar Agustin (FKIP Universitas Muhammadiyah Sukabumi, 2018)
The aims of this study are to earn an effective career guidance program in increasing students career choiceability for 10th-grade students in 14 Senior High School. The approach of this study used in quantitative with quasi-experimentmethods and nonequivalent pretest-posttest control group design as a research design. The researchinstrument is the non-test model which used rating scale questionnaire. A parametric statistic was used as a technique ofdata analysis to measure paired sample t-test. This study shows: 1) the general profile of students career choice ability;2) the formula of suitable for career guidance program according to expert and practitioner; and 3) the effectiveness ofcareer guidance program to increase students career choice ability.Keywords: Program of Career Guidance, Career Choice ability